The Dynamics of Indonesia's Beef Imports Over the Past Three Decades and the Influencing Factors - Pertiwi, Rahima; Yuzaria, Dwi; Sartika, Winda (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2025)
The main issue in Indonesia’s beef sector over the past three decades is the inability of domestic production to meet national consumption needs, resulting in dependence on beef imports. Domestic price fluctuations, consumption growth outpacing production, and rising per capita income have also influenced the supply and demand dynamics of beef, affecting price stability and the welfare of local farmers. This study analyzes the dynamics of Indonesia’s beef imports and the factors influencing them during the 1993–2022 period using annual time series data. A quantitative approach with the Ordinary Least Squares (OLS) method was employed to examine the effects of production, consumption, domestic price, foreign price, exchange rate, and per capita income on beef import volume. The results show that production, consumption, domestic price, and per capita income significantly affect the volume of beef imports, while foreign price and exchange rate do not have a significant impact. This study recommends policies that support sustainable increases in domestic production and control of domestic prices to ensure affordability for consumers without harming local farmers. The findings can serve as a basis for the government to formulate strategies for animal food security by strengthening supply chains, improving distribution efficiency, and enhancing the productivity of smallholder farmers to maintain the stability of Indonesia’s beef market.